Optimization Design of SNS Sensor Structural Parameters for Battery Expansion Monitoring - Xu, Shibo; Wang, Zhe; Yang, Hanrui; Jiao, Shengxi; Liu, Jien; Shang, Zhiyuan (Frontiers in Energy Research, 2021)
In this article, a method to improve refractive index (RI) sensitivity of single‐mode–no core–single‐mode fiber (SNS) sensor structure is addressed by optimization of geometric parameters of no-core fiber (NCF), which could be used to accurately measure the irreversible deformation of the battery expansion state caused by temperature change. From the perspective of temperature changing RI of the electrolyte solution, the impacts of diameter, length, and waveband on the performance of the fiber sensor have been discussed as RI measurement range is 1.340–1.390. After optimization, RI sensitivity can reach approximately 2,252.7 and 2037.3 nm/RIU with the length of 6.55 and 6.75 mm when the RI is from 1.380 to 1.390.